Artificial Intelligence - Kaushik, Saroj (Delhi Cengage Learning India, 2011)
Exploring artificial intelligence, this book covers topics like neural networks and robotics. It examines the range of problems which have been and remain to be solved using Artificial Intelligence tools and techniques.
Include Reference and Index
Keywords: Artificial intelligence